2011
DOI: 10.1097/mpg.0b013e3182243aa7
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition Changes in Preterm Infants Following Hospital Discharge

Abstract: Markedly lower FFM and higher adiposity were observed in preterm infants at term CA, but these differences had lessened and were no longer statistically significant at 3 to 4 months CA. Although early nutrition was associated with growth trajectories in the hospital, the continuing influence of early illness on postdischarge growth suggests that nonnutritional factors (eg, disturbances in the growth hormone axis) also may affect body composition trajectories of preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
88
2
18

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(124 citation statements)
references
References 40 publications
(52 reference statements)
16
88
2
18
Order By: Relevance
“…It has been found that extremely preterm infants, including those born small for gestational age, show a major deposition of fat mass in early postnatal life so that they show an increased adiposity at term-corrected age (7,14). However, within the first 3-4 mo of corrected age, extremely preterm infants succeed in achieving fat mass values similar to those of full-term infants (9,15).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that extremely preterm infants, including those born small for gestational age, show a major deposition of fat mass in early postnatal life so that they show an increased adiposity at term-corrected age (7,14). However, within the first 3-4 mo of corrected age, extremely preterm infants succeed in achieving fat mass values similar to those of full-term infants (9,15).…”
Section: Discussionmentioning
confidence: 99%
“…When body composition of former preterm infants at corrected fullterm age is compared with that of full-term infants, fat mass is equivalent or greater and fat-free mass is less in former preterm infants, resulting in higher body fat percentage estimates. 10,50,59 As body composition data for preterm infants become available, relationships between weight-forlength ratios, body composition, and outcomes must be explored.…”
Section: Figurementioning
confidence: 99%
“…In a meta-analysis of eight studies of infants with a mean gestational age of 30.0 wk, the body composition at term-equivalent age exhibited less lean tissue but more similar fat mass (and therefore higher %BF) than infants born at term (34). Ramel et al also investigated the body composition of preterm AGA infants born at 31.5 wk of gestation and term AGA infants at term-equivalent age (35), and observed markedly lower fat-free mass and higher adiposity in preterm infants. In addition, Giannì et al investigated changes in the body composition of late preterm AGA infants at gestational age 35.2 wk in a cohort study from birth (36).…”
Section: Preterm Aga Vs Term Aga Infantsmentioning
confidence: 99%